The RNA-binding Motif Protein 15B (RBM15B/OTT3) Acts as Cofactor of the Nuclear Export Receptor NXF1 - Uranishi, Hiroaki (American Society for Biochemistry and Molecular Biology, 2009)
The human SPEN family proteins SHARP, RBM15/OTT1, and RBM15B/OTT3 share the structural domain architecture but show distinct functional properties. Here, we examined the function of OTT3 and compared it with its paralogues RBM15 and SHARP. We found that OTT3, like RBM15, has post-transcriptional regulatory activity, whereas SHARP does not, supporting a divergent role of RBM15 and OTT3. OTT3 shares with RBM15 the association with the splicing factor compartment and the nuclear envelope as well as the binding to mRNA export factors NXF1 and Aly/REF. Mutational analysis revealed direct interaction of OTT3 and RBM15 with NXF1 via their C-terminal regions. Biochemical and subcellular localization studies showed that OTT3 and RBM15 also interact with each other in vivo, further supporting a shared function. Genetic knockdown of RBM15 in mouse is embryonically lethal, indicating that OTT3 cannot compensate for the RBM15 loss, which supports the notion that these proteins, in addition to sharing similar activities, likely have distinct biological roles.